2020
DOI: 10.18502/jfrh.v14i3.4674
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pregnancy after Elimination of Embryo Fragments Before Fresh Cleavage-Stage Embryo Transfer

Abstract: Objective: To determine if the elimination of fragments in cleavage-stage embryos, before fresh transfer, improves pregnancy rates in in vitro fertilization cycles. Materials and methods: This is a Prospective observational case-control study carried out at a University Reproductive Center. We included Twenty-six infertile patients divided into two groups. Group one: 13 patients with embryos classified as grade B and C (embryos with fragments) according to the Hill classification, and Group two: 13 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Sordia-Hernandez and colleagues reported results in line with this idea, but they also observed a higher rate of abortions in the group of patients who had defragmented embryos transferred. The relationship between micromanipulation and abortion is controversial and could be related to the fact that fragmented embryos could be genetically abnormal, or they could suffer important structural damage when fragment aspiration is performed [111,112]. Taken together, positive implantation outcomes after microsurgical fragment removal could be the result of the restoration of spatial relationship of cell-to-cell contacts disturbed by fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Sordia-Hernandez and colleagues reported results in line with this idea, but they also observed a higher rate of abortions in the group of patients who had defragmented embryos transferred. The relationship between micromanipulation and abortion is controversial and could be related to the fact that fragmented embryos could be genetically abnormal, or they could suffer important structural damage when fragment aspiration is performed [111,112]. Taken together, positive implantation outcomes after microsurgical fragment removal could be the result of the restoration of spatial relationship of cell-to-cell contacts disturbed by fragments.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that ZP is not always necessary for normal embryo development since the ZP-free embryos developed normally, maintained their cell adhesions, and had a decreased rate of fragmentation [ 96 ]. It seems that defragmentation of an aneuploid or severely fragmented embryo, only improves the embryo morphology grade but the quality and fate of embryo is not changed [ 97 ].…”
Section: Resultsmentioning
confidence: 99%